2002
DOI: 10.1016/s0140-6736(02)11042-7
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab for idiopathic membranous nephropathy

Abstract: Treatments for idiopathic membranous nephropathy, a common cause of nephrotic syndrome, can be very toxic. In view of the pathogenic potential of B cells in this disease, we studied the effects of four weekly infusions of rituximab (375 mg/m(2)-- the monoclonal antibody to B-cell antigen CD20--in eight patients who had idiopathic membranous nephropathy with persistent nephrotic syndrome. At weeks 4 and 20, urinary protein decreased from mean (SE) 8.6 g/24 h (1.4) to 3.8 (0.8) and 3.7 (0.9), respectively (p<0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
234
2
11

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 325 publications
(258 citation statements)
references
References 5 publications
11
234
2
11
Order By: Relevance
“…36 Small studies have separately characterized efficacy of the anti-CD20 agent rituximab in treatment of chronic graft-versus-host disease, 37 and idiopathic membranous glomerulonephritis. [38][39][40][41] Thus, it is not unexpected that rituximab-treated hematopoietic cell transplantation recipients with biopsy proven membranous glomerulonephritis responded well (three allogeneic and one autologous transplant). Although other reports have demonstrated treatment response with rituximab in hematopoietic cell transplantation patients with membranous glomerulonephritis/nephrotic syndrome, many previously reported patients had only partial remission, and in one case a biopsy was not performed.…”
Section: Discussionmentioning
confidence: 99%
“…36 Small studies have separately characterized efficacy of the anti-CD20 agent rituximab in treatment of chronic graft-versus-host disease, 37 and idiopathic membranous glomerulonephritis. [38][39][40][41] Thus, it is not unexpected that rituximab-treated hematopoietic cell transplantation recipients with biopsy proven membranous glomerulonephritis responded well (three allogeneic and one autologous transplant). Although other reports have demonstrated treatment response with rituximab in hematopoietic cell transplantation patients with membranous glomerulonephritis/nephrotic syndrome, many previously reported patients had only partial remission, and in one case a biopsy was not performed.…”
Section: Discussionmentioning
confidence: 99%
“…Rituximab binds to the surface of CD20-positive B cells with subsequent activation of the complement system mediating complement-dependent cellular cytotoxicity. In addition, rituximab mediates antibody-dependent cellular cytotoxicity through Fc-receptor binding [53][54][55][56]. However, B-cell depletion per se cannot alone explain the response to rituximab, as B-cell depletion occurs in all treated patients irrespective of the time to response and irrespective of clinical response to rituximab.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research by Beck et al has shown that 70% of patients with idiopathic membranous nephropathy have an auto-antibody to the Mtype phospholipase A2 receptor (PLA2R) that is present on podocytes [9]. Initial studies of RTX in patients with membranous nephropathy demonstrated a variable response, though there were some subjects that had significant improvement [62]. Like many of the other disease processes described, current treatment strategies include steroids, cyclophosphamide and other immunosuppressants, such as calcineurin inhibitors and mycophenolate mofetil.…”
Section: Idiopathic Membranous Nephropathymentioning
confidence: 99%